Analysis of the applicative potential of pigments extracted from bacterial isolates of mangrove soil as topical UV protectants (Brazilian Journal of Pharmaceutical Sciences, 2022)
Antioxidant, antibacterial and UV protective activities of two pigments extracted from mangrove soil isolates were analysed for their applications as ingredients in sunscreen formulations. Through biochemical characterization, the isolates were tentatively identified as belonging to the Flavobacterium sp. and Brevibacterium sp. UV visible spectral characterization of the pigments indicated presence of carotenoids. The orange pigment exhibited Sun Protection factor (SPF) value of 5.3 while the yellow pigment SPF was found to be 2.60. Both isolates as well as their pigments revealed tolerance to UVA-B radiation and to UVC radiation, to comparatively lesser extent. Yellow pigment exhibited good antibacterial activity with maximum effect on Escherichia coli, Corynebacterium diptheriae and Staphylococcus aureus. Both pigments were capable of reducing DPPH radical with % DPPH inhibition of 52.36% (orange pigment) and 40.1% (yellow pigment). These findings suggest that both pigments show promise of making excellent natural components of cosmetic formulations, especially sunscreens.